(untitled) (Rivista Italiana di Filosofia Analitica Junior, 2014)
This paper deals with ascriptions of collective responsibility and the distribution of the responsibility from the group to the individuals. Specifically, this article proposes a solution to cases of collective responsibility which is also sensitive to the demands of normative individualism. The article contends that Judith Jarvis Thomson’s concept of a Minimally Decent Samaritan is a valuable tool for the correct ascription of responsibility to individuals from collectives as it is neither excessively demanding, like Arendt’s and Jaspers’ accounts, or not emanding enough. It is contended that being a Minimally Decent Samaritan is enough to distance oneself from the group and, hence, avoid being held responsible.